The HIGH FLOW OXYGEN THERAPY MACHINE USING HIGH FLOW NASAL CANNULATION A HOPE FOR COVID-19 PATIENTS IN ACUTE RESPIRATORY FAILURE - Khoso, Ali Raza (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
OBJECTIVE: To provide humidified, heated and precis oxygen with high efficiency of Functional residual to acute respiratory distress syndrome patients caused by COVID-19. METHODOLOGY: It was an observational research that took place at the LUMHS Hospital. In this study, 200 patients with severe respiratory distress, either caused by Covid-19 or other respiratory disorders, were enrolled. LUMHS hospital ICU ward was used as a data source. This study showed that subjects in late 30s, both male and female. Patients with acute or chronic respiratory failure were included, but those with other pulmonary disorders were excluded. RESULTS: A total of 200 patients were selected for this study. Out of them 122 (61%) were males and 78 (39%) were females with the Standard deviation of 2.33. Regarding to age. 24%. Were below 30s. 20% patients were in 30s.and 57% belonged to above 30s. While the efficiency of HFNC was 65%. in 65% cases it was proved to be lifesaving and in 39% cases patients were sent for intubation. Oxygen delivery method using cannula was 65% in delivering SPO2 equal to or greater than 10lpm while face mask method was only 35% successful that determines for higher concentration cannulation is more efficient method than face mask. CONCLUSION: HFNC is a recent innovation that reduces the need for intubation and oxygen loss while also providing high-flow oxygen with optimum humidification and temperature to patients with respiratory failure